The Sage dictionary of health and society - White, Kevin, 1955-; Sage eBooks (London : SAGE, 2006)
The field of health studies has grown enormously over the last 25 years. This volume covers over 900 terms commonly used in the health studies field.
Specialized.
Description based on print version record.
Includes index.
Keywords: Social medicine -- Dictionaries; Electronic books